Analysis of Medical Personnel Performance Factors in Filling Out Outpatient Medical Record Documents at Dental and Mouth Hospital Gusti Hasan Aman - Teguh Hadianto; Syamsul Arifin; Eko Suhartono (Universitas Malahayati Lampung, 2025)
ABSTRACT Medical records are very important documents in the health care system, serving to record and store patient health information. Accurate and complete medical record filling is highly dependent on the performance of medical personnel. However, there are often challenges in filling out medical records caused by various factors, including knowledge, available facilities, and motivation of medical staff. This study aims to analyze the influence of knowledge, facilities, and work motivation on the performance of medical personnel in filling out medical record documents for outpatients at RSGM Gusti Hasan Aman. By understanding this relationship, it is expected to provide recommendations to improve the quality of medical record filling. This study used a quantitative approach with a cross-sectional design. The study subjects consisted of 54 medical personnel, including general dentists and specialists, working at RSGM Gusti Hasan Aman. Data were collected through a questionnaire designed to measure the variables of knowledge, facilities, and work motivation. Data were analyzed using descriptive and inferential statistics, including Chi-square test and multiple logistic regression. The analysis showed that there was a significant relationship between knowledge (p=0.001), facilities (p=0.001), and work motivation (p=0.004) with the performance of medical personnel in filling out medical record documents. Among the three variables, facilities proved to be the most dominant factor in influencing the performance of medical staff. Improving the knowledge and work motivation of medical personnel, as well as providing adequate facilities, is essential to improve the quality of medical record filling. Recommendations for hospital management include continuous training for medical personnel and improvement of health facility infrastructure. Keywords: Medical Records, Medical Staff Performance, Knowledge, Facilities, Work Motivation.